Physics for Matriculation - Poh, Liong Yong (Oxford Fajar Sdn. Bhd., 2014)
Physics for Matriculation Semester 2 Fourth Edition Updated is a comprehensive coursebook written for students studying Physics in local matriculation colleges. It is based on the Matriculation Physics SF026 syllabus issued by the Matriculation Division, Ministry of Education, Malaysia. This coursebook aims to stimulate students' interest in physics and help them gain a firm understanding of important principles and concepts in physics. In addition, it helps students prepare for their Physics examination.